(untitled) (JÓVENES EN LA CIENCIA, 2021)
Education has suffered from drastic changes due to the recent COVID-19 pandemic. This investigation is a self-research study conducted by three foreign language students. The purpose of this research is to investigate how the new online learning modality affected language learning. This research focuses on cooperative learning and peer interaction in an online setting. This self-study research project will present the results of the longitudinal study carried out over eight months by students in a BA in English language teaching at the University of Guanajuato. The students were enrolled in foreign language learning classes, and data were collected in a Sway portfolio, using reflective journal entries and visual evidence. The data analysis presents qualitative results showing that online learning has negative effects on peer interaction, such as the feeling of loneliness and isolation. The results allowed us to obtain a major awareness about online learning and its challenges, as well as to reflect about the importance of peer interaction in language learning.